Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1381/096089206775222104
|View full text |Cite
|
Sign up to set email alerts
|

Is Routine Preoperative Upper Endoscopy in Gastric Banding Patients Really Necessary?

Abstract: The data suggest that it may not be necessary to continue performing gastroscopy in all patients preparing for gastric banding. The data collected support the policy of a selective use of gastroscopy, only focusing on patients suffering from gastroesophageal symptoms. By following this strategy, the rate of preoperative gastroscopies can be reduced safely by 80%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 8 publications
0
26
1
Order By: Relevance
“…Increasing BMI is positively correlated with vomiting, upper abdominal pain, and constipation, thus supporting a more selective approach to screening based on UGI symptoms [23]. Moreover, Korenkov et al suggest that an 80% reduction in the rate of preoperative EGD can be achieved by limiting this procedure to patients who have UGI symptoms [13]. The overall prevalence of findings in all their patients was only 10%, but symptomatic patients had a significantly higher yield of findings (67%) at EGD compared to patients without symptoms who had an extremely low yield (2%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing BMI is positively correlated with vomiting, upper abdominal pain, and constipation, thus supporting a more selective approach to screening based on UGI symptoms [23]. Moreover, Korenkov et al suggest that an 80% reduction in the rate of preoperative EGD can be achieved by limiting this procedure to patients who have UGI symptoms [13]. The overall prevalence of findings in all their patients was only 10%, but symptomatic patients had a significantly higher yield of findings (67%) at EGD compared to patients without symptoms who had an extremely low yield (2%).…”
Section: Discussionmentioning
confidence: 99%
“…Additional sedation issues for the morbidly obese include postprocedure nausea and vomiting, which can be lessened with anesthesiologist-administered propofol as compared to endoscopist-administered benzodiazepines [8]. Prior studies in the literature have suggested that significant findings are detected in approximately one third of patients undergoing preoperative EGD [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Chromogranin A has been described as a biochemical marker in patients with gastric carcinoids, used for disease diagnosis and monitoring [3,13,16]. Many articles have described upper endoscopy as an important tool in bariatric surgery [21][22][23][24][25][26]. After surgery, the gastric remnant becomes inaccessible to conventional endoscopic examinations, denoting the importance of the endoscopic procedure before bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the indication for the implantation of the SAGB was correct since a protective effect of SAGB for GERD has been advocated years ago provided a normal esophageal peristalsis [8]. A preoperative evaluation of the gastroesophageal junction is still under debate and until presently no generally accepted approach is defined [8,[11][12][13].…”
Section: Discussionmentioning
confidence: 99%